Correction: An evidence for an organic N-doped multiwall carbon nanotube heterostructure and its superior electrocatalytic properties for promising dye-sensitized solar cells. Issue 18 (30th April 2018) - Arbab, Alvira Ayoub; Memon, Anam Ali; Sahito, Iftikhar Ali; Mengal, Naveed; Sun, Kyung Chul; Ali, Mumtaz; Jeong, Sung Hoon
Abstract : Correction for 'An evidence for an organic N-doped multiwall carbon nanotube heterostructure and its superior electrocatalytic properties for promising dye-sensitized solar cells' by Alvira Ayoub Arbab et al., J. Mater. Chem. A, 2018, DOI: ;10.1039/c8ta00535d .